Adaptabilidade e estabilidade de híbridos de milho e cultivares de trigo e soja em rede de ensaios - Rosa, Guilherme Bergeijer da (2025)
The optimization of agricultural resource use is essential for the sustainability of production systems. In a country characterized by a wide diversity of edaphoclimatic conditions, such as Brazil, the development of genotypes adapted to different environments is imperative. In this context, the proper placement of each genetic material in conditions where it expresses its maximum yield potential is crucial to enhance crop efficiency and stability. The objective of this study was to evaluate the placement of maize hybrids in a subtropical region using the Eberhart and Russell and AMMI methods. In addition, we aimed to assess whether the most widely sown cultivars in Rio Grande do Sul coincide with those selected by the methods, using the area allocated to soybean and wheat seed production as an indicator of farmer preference. Furthermore, an analysis of adaptability, stability, and grain yield parameters obtained by different methods over time was performed. For this purpose, multi-environment trial data from maize, soybean, and wheat conducted across different years in Rio Grande do Sul, Brazil, were used. Results indicated that the Eberhart and Russell and AMMI methods partially agreed in positioning maize hybrids for subtropical environments. The seed production area proved to be an indirect indicator of selection effectiveness and cultivar adoption for soybean and wheat. Parameter repeatability was limited by interannual variability of edaphoclimatic conditions, with grain yield being the only parameter that showed consistent correlation across three consecutive seasons for soybean cultivars. Despite these challenges, some cultivars performed positively in the subtropical context. However, further studies involving a larger number of locations, cultivars, and cropping seasons are required to deepen the understanding of the effectiveness of these methods and the repeatability of yield, adaptability, and stability parameters.